Looking back in wonder : diary of a dance critic - Sorell, Walter, 1905-1997. 4 0 16; 5 (New York : Columbia University Press, 1986)
Walter Sorell reminisces about nearly four decades of dance in America. His essays describe performers and performances and reflect on the artistic aspects of dance and choreographers.
Includes index.
Library Journal, January 2010;Library Journal
Adult;Adult
Keywords: 2 -- Sorell, Walter, -- 0 -- 1905-1997.; 6; Dance critics;Sorell, Water,;Dance critics -- 1905-1997. -- United States -- Biography.;Biography.; 20; 2